South Asian transnational marriages in comparative perspective - CHARSLEY, KATHARINE; SHAW, ALISON (Global Networks, 2006)
Abstract This issue on South Asian transnational marriages brings diverse practices and networks into detailed ethnographic focus. Gender and agency are key themes explored in the collection, as well as the potential and actual transformation of gendered status resulting from marrying a migrant or joining a spouse overseas. The introduction identifies some common threads. Several articles challenge the assumption of wives' passivity in arranged marriages or in their joining husbands overseas, while one highlights the less-documented experiences of men who migrate to join wives working abroad. The collection also offers insights into the cultural and emotional reasons for such marriages, complementing analyses that stress strategic motivations, and noting the emotional consequences of separation and new household formations for the experiences of marriage and parenthood. Marriage emerges as an important means of producing and transforming transnational networks, while marriage practices and dynamics are themselves transformed in the process.
Keywords: 2000 à aujourd'hui; 2000-2009; anthropologie; approches et analyses; asie; asie du sud; cours; discipline; ethnographie; histoire et politique; mariage; migration; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

Transnational migration theory in population geography: gendered practices in networks linking Canada and India - Walton-Roberts, Margaret (Population, Space and Place, 2004)
Geographers have recently suggested that transnational migration theory can contribute to the development of a critical population geography. What might such a critical population geography look like? In this paper I explore this in three ways. Firstly I offer some comments on why geographers have been slow to adopt a transnational focus on migration, and secondly I examine how gender has been underplayed in transnational literature. Thirdly I draw upon some examples from research on transnational immigrant networks between Canada and India. I focus on the specifics of Punjabi marriage migration networks to demonstrate how the practice of spousal selection has become globalised for certain diasporic communities. These examples offer a preliminary illustration of what a critical population geography, attuned to issues of gendered transnational processes, might contribute to current debates. Copyright © 2004 John Wiley & Sons, Ltd.
Keywords: amériques; approches et analyses; asie; canada; cours; discipline; géographie; histoire et politique; inde; mariage; mariages transnationaux; migration; premier cycle; punjab; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs -- qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those -- the vast majority -- who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe